2018
DOI: 10.4236/am.2018.92013
|View full text |Cite
|
Sign up to set email alerts
|

Point Transformations and Relationships among Linear Anomalous Diffusion, Normal Diffusion and the Central Limit Theorem

Abstract: We present new connections among linear anomalous diffusion (AD), normal diffusion (ND) and the Central Limit Theorem (CLT). This is done by defining a point transformation to a new position variable, which we postulate to be Cartesian, motivated by considerations from super-symmetric quantum mechanics. Canonically quantizing in the new position and momentum variables according to Dirac gives rise to generalized negative semi-definite and self-adjoint Laplacian operators. These lead to new generalized Fourier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…We recently showed that a wide class of anomalous diffusion systems were, in fact, normal diffusion systems when one interpreted the solution to the diffusion equation using the appropriate generalized canonically conjugate position and momentum 4 .…”
Section: An Implication Of the ĥW Generalized Harmonic Oscillators Fo...mentioning
confidence: 99%
“…We recently showed that a wide class of anomalous diffusion systems were, in fact, normal diffusion systems when one interpreted the solution to the diffusion equation using the appropriate generalized canonically conjugate position and momentum 4 .…”
Section: An Implication Of the ĥW Generalized Harmonic Oscillators Fo...mentioning
confidence: 99%